2017
DOI: 10.1103/physrevb.95.024415
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring magnetic energies to form dipole skyrmions and skyrmion lattices

Abstract: The interesting physics and potential memory technologies resulting from topologically protected spin textures such as skyrmions, has prompted efforts to discover new material systems that can host these kind of magnetic structures. Here we use the highly tunable magnetic properties of amorphous Fe/Gd multilayer films to explore the magnetic properties that lead to dipole-stabilized skyrmions and skyrmion lattices that form from the competition of dipolar field and exchange energy. Using both real space imagin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
158
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 61 publications
15
158
0
Order By: Relevance
“…We demonstrate the realization of an ordered magnetic skyrmion lattice in amorphous multilayer thin-films without DM interactions. These skyrmions have been suggested to be stabilized by dipole-dipole interactions, 19,20 but recent works have suggested a random anisotropy (RA) specific to amorphous and nanocrystalline systems may also contribute to skyrmion formation 21 . Utilizing a straight forward magnetic field sequence (presented in Supplemental Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate the realization of an ordered magnetic skyrmion lattice in amorphous multilayer thin-films without DM interactions. These skyrmions have been suggested to be stabilized by dipole-dipole interactions, 19,20 but recent works have suggested a random anisotropy (RA) specific to amorphous and nanocrystalline systems may also contribute to skyrmion formation 21 . Utilizing a straight forward magnetic field sequence (presented in Supplemental Fig.…”
Section: Introductionmentioning
confidence: 99%
“…SKBs are topologically equivalent to magnetic skyrmions and exhibit similar topological properties, such as the topological Hall effect, 27 skyrmion Hall effect, 33 and ultra-low driving current density for current-induced motion. 25 More importantly, SKBs show a significantly high thermal stability over a wide temperature range crossing room temperature, 27,28,34 showing a high potential of SKBs for the construction of memory devices.Contrary to DMI-stabilized skyrmions with a fixed helicity, SKBs in centrosymmetric magnets possess two degrees of freedom, i.e., vorticity and helicity, 35 which makes them usually coexist with the topologically trivial bubbles (topological number is equal to 0), [28][29][30][31]37 or exhibit multiple topologies such as biskyrmions, 25,27,30,36 and various metastable SKBs 28,30,36 (for example, pendulum-shaped SKBs 29 and bifurcation-shaped SKBs 28,30,36 ).When external stimuli, such as magnetic field H or spin-polarized current, are applied, the spin structures of the trivial and metastable SKBs may vary with the motion of Bloch lines (BLs), making them unsuitable for the application in magnetic racetrack memory devices.Therefore, in order to be suitable for such applications, it is essential to remove trivial bubbles and metastable SKBs. 21Recent theoretical simulations, based on the nanostructured frustrated magnet, showed that the periodically modulated spin textures at geometrical boundaries had a significant influence on the magnetization dynamics of SKBs , 35 offering a new path that designing proper…”
mentioning
confidence: 99%
“…Contrary to DMI-stabilized skyrmions with a fixed helicity, SKBs in centrosymmetric magnets possess two degrees of freedom, i.e., vorticity and helicity, 35 which makes them usually coexist with the topologically trivial bubbles (topological number is equal to 0), [28][29][30][31]37 or exhibit multiple topologies such as biskyrmions, 25,27,30,36 and various metastable SKBs 28,30,36 (for example, pendulum-shaped SKBs 29 and bifurcation-shaped SKBs 28,30,36 ).…”
mentioning
confidence: 99%
“…To move beyond dislocations and disclinations in wPMA materials, alternative strategies would be required, and they have only begun to be explored. This has been done, for example, by the application of out-of-plane magnetic fields in order to drive a transition from stripe pattern to dipolar skyrmion in amorphous Fe/Gd multilayers [31]. Other possibilities could be based in domain imprinting, as it is often done in multilayers that combine in-plane and out-of-plane anisotropy layers [16], or in geometrical confinement by sample patterning [32].…”
Section: Introductionmentioning
confidence: 99%